Developing New Lab Base Teaching Approach for Linear Algebra subject in Engineering Mathematics Courses / N. Lohgheswary ...[et al.] - Lohgheswary, N.; Abdul Halim, M. H.; M. Nopiah, Z.; A. Aziz, A.; Zakaria, E. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The underachievement of engineering students in engineering mathematics is due to poor prior knowledge and anxiety towards mathematics. This study aim to develop a new lab based teaching approach for engineering mathematics students in Universiti Kebangsaan Malaysia (UKM) via computing applications. This has called for the investigation of the curriculum of engineering mathematics or in specific, the syllabus of the content of Linear Algebra in UKM. The Linear Algebra syllabi in 61 universities were compared with the UKM's 14 weeks' Linear Algebra syllabus. The eight highest percentages of common topics in Linear Algebra were identified. Matrix and basic operations, application in linear system, vector space and subspace, eigen value and eigen vector, diagonalization and series are the eight topics which will be taught in lab sessions in computing language. To justify these findings, many researchers have been using various computing tools such as Mathcad, Maple and MATLAB to